2018
DOI: 10.21608/ejdr.2018.3236.1004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidants and Potassium on Productivity of Sunflower in Sandy Soil

Abstract: uring two summer seasons of 2015 and 2016, the influence of antioxidants application and potassium levels on productivity of sunflower was estimated under sandy soil conditions. Antioxidants (nil antioxidants; tap water only; vitamin E, 50 ppm; vitamin C, 100 ppm; citric acid, 500 ppm and vitamin E + vitamin C + citric acid at the same levels used individually for each). Potassium levels included 0, 24, 36 and 48 kg K 2 O/feddan (0.42 hectar). Results showed that both antioxidants application and potassium lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…by, Citric acid. This results in agreement with those reported by Sakr andArafa (2009), El-Sabagh et al (2017) and the similar trend was found in sunflower by Salem and Shoman (2018). Where: * and ** mean significant at 5 and 1 % level of probability, respectively.…”
Section: -Seed Oil Content and Oil Yield Traitssupporting
confidence: 93%
See 3 more Smart Citations
“…by, Citric acid. This results in agreement with those reported by Sakr andArafa (2009), El-Sabagh et al (2017) and the similar trend was found in sunflower by Salem and Shoman (2018). Where: * and ** mean significant at 5 and 1 % level of probability, respectively.…”
Section: -Seed Oil Content and Oil Yield Traitssupporting
confidence: 93%
“…This increase may be due to increasing all yield attributes under this study by antioxidants foliar spray especially, Citric acid. These results are in the same trend with those reported by El-Sabagh et al (2017), and Salem and Shoman (2018).…”
Section: -Seeds Weight /Plant and Fed Traitssupporting
confidence: 92%
See 2 more Smart Citations
“…While certain fatty acid concentrations remained unaffected, potassium-deficient sunflowers exhibited reduced yield and oil content. Salem (2018) reported that potassium treatment significantly improved sunflower growth parameters, with the highest values observed at 48 kg ha-1 K. Capitulum diameter, seed number per capitulum, and seed yield were highest at this potassium level. Antioxidant treatment and potassium levels interaction influenced most attributes, except for harvest index and seed protein %.…”
Section: Literature Reviewmentioning
confidence: 84%